BACTERIAL AND MACROINVERTEBRATE COMMUNITY STRUCTURE IN RELATION TO PHYSICOCHEMICAL PARAMETERS OF WATER IN THREE RIVERS IN BOSNIA AND HERZEGOVINA - Gajević, Mahir; Đug, Samir; Mušović, Aldijana; Hasić, Azemina; Matović, Maja; Crnovršanin, Elma; Bešta-Gajević, Renata (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
In this paper, the physicochemical and biological parameters in three rivers of Bosnia and Herzegovina are investigated. The compositions of macrozoobenthos and bacterial communities in the rivers Drina, Gostović and Vogošća were analyzed. Data were obtained by field sampling conducted during the summer period in 2019 and 2020. Results indicate that the most of the physicochemical parameters of water change with the impact of pollution and altitude. The results showed that the structure of macroinvertebrate communities, the number of indigenous or allochthonous bacterial populations in the examined rivers significantly depends on altitude, temperature and oxygen concentration. Patterns of correlation were observed between individual physicochemical parameters of water on the one hand and communities of macroinvertebrates and bacteria on the other.